Well-being among the Elderly - challenges for social policy - Marzanna, (Magyar Gerontológia, 2025)
The aim of this presentation is to explore the multidimensional concept of well-being among older adults and to identify the factors that can either support or threaten it. In the context of an aging society, the issue of quality of life in late adulthood is gaining increasing importance not only from an individual perspective, but also systemically as a challenge for social policy, healthcare, and local communities.